Firm Size, Business Risk, Asset Structure, Profitability, and Capital Structure - Komang Ayu Tri Handayani; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2018)
ABSTRACTThe aim of this study is to determine the effect of firm size, business risk, asset structure,  and  profitability  as  well  as  its  impact  on  capital  structure.  This  study  uses secondary data in the form of corporate financial statements. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange period 2015-2016. By using purposive sampling method, then obtained amount of sampel counted 69 companies. The analysis technique used is path analysis. The results showed that firm size and business risk have a significant positive effect on profitability, while asset structure has no effect on profitability. Company size have significant positive effect to capital structure, profitability have significant negative effect to capital structure, while business risk and asset structure have no effect to capital structure.